Pendampingan Penyusunan Laporan Keuangan Usaha Tani di Kabupaten Singkawang Timur (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to improve the ability of farmers in East Singkawang Regency to prepare simple and structured financial reports. Prior to the activity, most farmers had not maintained regular financial records, thus experiencing difficulties in identifying production costs, revenue, and profitability. The implementation method included socialization of farm financial management, training in preparing simple financial reports, and intensive mentoring. This activity involved 20 farmers as community service partners. Evaluation was conducted through comparing conditions before and after the activity using pre- and post-test instruments and observing financial record keeping results. The results showed a 45% increase in farmers' understanding of financial reporting concepts, as well as a 50% increase in their ability to prepare simple profit and loss and cash flow statements. Furthermore, 83% of participants were able to record business transactions independently and sustainably after the mentoring activity. The implementation of simple financial reports also helped farmers identify production cost structures and determine business plans for the next planting season. This community service activity contributed to strengthening the application of financial management in farming businesses and supported increased transparency, efficiency, and economic sustainability for farmers in East Singkawang Regency.